tRNA-Derived Fragments as Novel Predictive Biomarkers for Trastuzumab-Resistant Breast Cancer - Chunxiao Sun; Fan Yang; Yanhong Zhang; Jiahui Chu; Jian Wang; Yifan Wang; Yanqiu Zhang; Jun Li; Yongfei Li; Ruihua Fan; Wei Li; Xiang Huang; et al. (Cellular Physiology and Biochemistry, 2018)
Background/Aims: Resistance to trastuzumab remains a common challenge to HER-2 positive breast cancer. Up until now, the underlying mechanism of trastuzumab resistance is still unclear. tRNA-derived small non-coding RNAs, a new class of small non-coding RNA (sncRNAs), have been observed to play an important role in cancer progression. However, the relationship between tRNA-derived fragments and trastuzumab resistance is still unknown. Methods: We detected the levels of tRNA-derived fragments expression in normal breast epithelial cell lines, trastuzumab-sensitive and -resistant breast cancer cell lines using high-throughput sequencing. qRT-PCR was conducted to validate the differentially expressed fragments in serums from trastuzumab-sensitive and -resistant patients. A receiver operating characteristic (ROC) curve analysis was performed to evaluate the power of specific tRNA-derived fragments. Progression-free survival (PFS) was analyzed using Cox-regression. Results: Our sequence results showed that tRNA-derived fragments were differentially expressed in the HBL-100, SKBR3, and JIMT-1 cell lines. tRF-30-JZOYJE22RR33 and tRF-27-ZDXPHO53KSN were found significantly upregulated in trastuzumab-resistant patients compared to sensitive individuals, and the ROC analysis showed that tRF-30-JZOYJE22RR33 and tRF-27-ZDXPHO53KSN were correlated with trastuzumab resistance. In a multivariate analysis, higher levels of tRF-30-JZOYJE22RR33 and tRF-27-ZDXPHO53KSN expression were associated with significantly shorter PFS in patients with metastatic HER-2 positive breast cancer. Conclusion: Our results suggest that tRF-30-JZOYJE22RR33 and tRF-27-ZDXPHO53KSN play important roles in trastuzumab resistance. Patients with high levels of tRF-30-JZOYJE22RR33 and tRF-27-ZDXPHO53KSN expression benefitted less from trastuzumab-based therapy than those that express lower-levels of these molecules. tRF-30-JZOYJE22RR33 and tRF-27-ZDXPHO53KSN may be potential biomarkers and intervention targets in the clinical treatment of trastuzumab-resistant breast cancer.